Quantitative Nuclear Magnetic Resonance Spectroscopic Analysis of Valsartan in Bulk and Solid Oral Dosage Form - Kalaimagal, A.; Hemalatha, P.V.; Jerad Suresh, A.; Udaya Kumar, G.S.; Niraimathi, V. (Asian Journal of Chemistry, 2013)
NMR spectroscopy has been applied to the quantification of valsartan in bulk and pharmaceutical dosage form. The estimation was carried out by proton nuclear magnetic resonance spectroscopy using tetra chloro nitro benzene as an internal standard and deuterated chloroform as the NMR solvent. NMR patterns were recorded for both valsartan and tetra chloro nitro benzene in deuterated chloroform. The signals corresponding to the chemical shifts of 1.73 and 4.95 ppm for valsartan and 7.75 ppm for tetra chloro nitro benzene were considered for quantification process.